Inspector Lewis. Series 7 [videorecording (DVD)] - Whately, Kevin; Fox, Laurence; Front, Rebecca; Holman, Clare; Dexter, Colin
DI Robert Lewis comes out of retirement to assist newly promoted DI James Hathaway investigate a series of crimes in and around Oxford.